1998
DOI: 10.1038/sj.ijo.0800555
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of research-based body composition techniques in healthy elderly men and women using the 4-compartment model as a criterion method

Abstract: OBJECTIVE: To examine the accuracy, precision and bias of body fat estimates using traditional research based techniques, relative to those derived from a 4-compartment model in healthy, older men and women. DESIGN AND SUBJECTS: Cross-sectional comparison of various body composition techniques in 41 healthy women (68.2 AE 6.6 y) and 41 healthy men (70.2 AE 7.0 y) with an age range of 57±90 y. METHODS: Fat mass (FM) by the 4-compartment (4C) model was compared to that derived by dual energy X-ray absorptiometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
42
1
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 19 publications
2
42
1
3
Order By: Relevance
“…18 Considered by many to be the 'gold standard' for estimating body fatness, DXA measurements have been limited to the research setting because of their complexity and cost. [19][20][21][22][23] Previous studies have reported significant associations between BMI and DXA 9,24,25 and a recent report in Pima Indian children showed significant relations for both BMI and DXA with blood pressure, lipids and fasting insulin.…”
Section: Introductionmentioning
confidence: 93%
“…18 Considered by many to be the 'gold standard' for estimating body fatness, DXA measurements have been limited to the research setting because of their complexity and cost. [19][20][21][22][23] Previous studies have reported significant associations between BMI and DXA 9,24,25 and a recent report in Pima Indian children showed significant relations for both BMI and DXA with blood pressure, lipids and fasting insulin.…”
Section: Introductionmentioning
confidence: 93%
“…These considerations have been reported as the main limitations of 2C model to assess body fat in elderly subjects (Baumgartner et al, 1991;Goran et al, 1998;Withers et al, 1999;Bosy-Westphal et al, 2003). Consequently, various investigators have recommended the use of multi-compartmental models to study body composition in elderly subjects (Heymsfield et al, 1989;Baumgartner et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…It is also known that the selection of the most appropriate equation should consider its validity within the population under study (15). The adequacy of Siri two compartment model for converting BD to %BF in older people has already been discussed (16,17). Previous studies have suggested that statements of Siri were appropriate for healthy old men but not for older women (16) and that Siri equation, depending on age, overestimates %BF by 2-3% in older individuals (17).…”
mentioning
confidence: 99%